FAMILY EXPERIENCES OF PREVENTING STUNTING AMONG CHILDREN UNDER TWO YEARS: A COMMUNITY HEALTH NURSING PERSPECTIVE - Sarifudin Andi Latif; Muhammad Syafri; Sahdan Mustari (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Stunting remains a major public health challenge affecting children's physical growth, cognitive development, and future productivity. Family involvement and community support are essential for effective prevention during the first 1,000 days of life. This study explored family experiences in preventing stunting among children under two years of age from a community nursing perspective in Jeneponto Regency, Indonesia. A qualitative descriptive phenomenological design was employed involving 14 purposively selected participants, including 10 mothers, two community nurses, and two Posyandu health volunteers. Data were collected through semi-structured in-depth interviews, field observations, and field notes, then analyzed using thematic analysis. Four themes emerged: family knowledge of stunting, family prevention practices, barriers to prevention, and community nursing support. Families practiced exclusive breastfeeding, nutritious complementary feeding, routine growth monitoring, and healthcare utilization. However, economic constraints, cultural beliefs, feeding difficulties, and limited healthcare access remained significant barriers. Family-centered community nursing interventions integrating education, empowerment, home visits, and multisectoral collaboration can strengthen sustainable stunting prevention among children under two years of age.